Britanny France by the French - Allain, Pierre-Henri (Hachette guide, 2000)
This guide to Brittany is full of information organized in topic-based spreads. Cultural history and heritage are combined with traditional holiday activities. Included are 35 discount vouchers offering reduced prices on presentation of the guide.